Rancangan Pemanfaatan Energi Baru Terbarukan Sebagai Sumber Energi di Desa Kelapa Patih Jaya Provinsi Riau - Nasution, Gaizka Ghifari; Dzaky, Muhammad Irfan (Politeknik Negeri Sriwijaya, Indonesia, 2023)
Indonesia is a country that has a variety of energy resources, both non-renewable and renewable. Development is progressing rapidly, as well as a very large population, of course resulting in a very large need for energy support. According to data owned by the World Bank, until 2020 alone Indonesia already has a population of 237.5 million. According to a report from the Riau Provincial Regional Energy General Plan (RUED-P) for 2020, the potential for New Renewable Energy (EBT) owned by the Province Riau itself consists of 6 types, namely geothermal, water, biomass, solar, wind and sea which can be utilized as electrical energy which is estimated to reach 5.9 gigawatts (GW). According to the Riau Energy and Mineral Resources (ESDM) Office, it is known that there are still 11 villages in Riau that did not have electricity until 2020, one of which is Kelapa Patih Jaya village. Based on the simulation using HOMER, the optimum hybrid power plant configuration is obtained consisting of 1 wind turbine and 10 batteries, with an inverter and biomass of 10 kW each